( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 6 + x 6 1 ) − 2
Find the minimum value of the expression above for positive x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same way! But theres a typo in your solution. In the last step you have written the maximum. It should be the minimum.
my solution is just same as yours .....thanks
i did same way
Let ( x + x 1 ) = m . . . . . . . ( 1 ) . Therefore ( x 3 + x 3 1 ) + 3 ( x + x 1 ) = m 3 ( x 3 + x 3 1 ) = m 3 − 3 m . . . . . . . ( 2 ) Squaring both sides , we get ( x 6 + x 6 1 ) = m 6 + 9 m 2 − 6 m 4 − 2 . . . . . . . . ( 3 ) Now rewriting the given expression in terms of m we get = m 3 + m 3 − 3 m m 6 − ( m 6 + 9 m 2 − 6 m 4 − 2 ) − 2 = 2 m 3 − 3 m 6 m 4 − 9 m 2 = 3 m By A . M − G . M x + x 1 ≥ 2 Therefore 3 m ≥ 6 .
Hence the minimum value of the given expression is 6
Nice solution! This question is there in the algebra material of the institute where I teach for IIT-JEE
Same method
Problem Loading...
Note Loading...
Set Loading...
( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 6 + x 6 1 ) − 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − [ ( x 3 + x 3 1 ) 2 − 2 ] − 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 3 + x 3 1 ) 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) [ ( x + x 1 ) 3 − ( x 3 + x 3 1 ) ] [ ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ] = ( x + x 1 ) 3 − ( x 3 + x 3 1 ) = x 3 + 3 x + x 3 + x 3 1 − x 3 − x 3 1 = 3 ( x + x 1 )
Using AM-GM inequality for x > 0 , we have x + x 1 ≥ 2 .
Then the maximum ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 6 + x 6 1 ) − 2 = 3 × 2 = 6